2006
DOI: 10.1080/00016340600627154
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence rate of endometriomas following a laparoscopic cystectomy

Abstract: Young age and severe endometriosis appeared to be the factors associated with high recurrence risk. Recurring ovarian endometrimas probably include cysts occurring spontaneously and those recurring from the cyst residues in the lesions where cystectomy has been performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
3
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 11 publications
5
52
3
6
Order By: Relevance
“…''Unfortunately, there is no permanent cure for this condition, so it often requires a life-long management plan with the goal of maximizing the use of medical treatment and avoiding repeated surgical procedures'', reports the American Society of Reproductive Medicine [3]. Lesions and symptoms very frequently return after medication is discontinued or after conservative surgery is performed, a fact which frustrates both patients and clinicians [4] and is estimated to occur in 30-50 % of cases within 2-5 years [2,[5][6][7][8][9][10]. The American College of Obstetricians and Gynecologists Practice Bulletin suggests that the true recurrence rate must be even higher than the rate generally reported in literature, because most publications report symptomatic disease only [11].…”
Section: Introductionmentioning
confidence: 99%
“…''Unfortunately, there is no permanent cure for this condition, so it often requires a life-long management plan with the goal of maximizing the use of medical treatment and avoiding repeated surgical procedures'', reports the American Society of Reproductive Medicine [3]. Lesions and symptoms very frequently return after medication is discontinued or after conservative surgery is performed, a fact which frustrates both patients and clinicians [4] and is estimated to occur in 30-50 % of cases within 2-5 years [2,[5][6][7][8][9][10]. The American College of Obstetricians and Gynecologists Practice Bulletin suggests that the true recurrence rate must be even higher than the rate generally reported in literature, because most publications report symptomatic disease only [11].…”
Section: Introductionmentioning
confidence: 99%
“…The surgical procedure for endometriosis used in our department has previously been described elsewhere. Briefly, we routinely performed the 4-puncture method under general anesthesia by endotracheal intubation in the lithotomy position [15,16]. In cases with endometriomas, we excised ovarian cyst walls-the so-called ''striping method''-and sewed purse-string sutures with Vicryl Ò 2-0 (Ethicon, Japan) in consideration of potential damage to the ovarian reserve.…”
Section: Laparoscopic Proceduresmentioning
confidence: 99%
“…Vercellini et al reported that the use of GnRH analogs prevents the risk of recurrence after surgery in patients with moderate or severe endometriosis (25). In contrast, some studies have been unsuccessful to show any evidence about the effects of post-operative medication in reducing endometriosis recurrence (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Recent findings demonstrated that post-surgical hormonal therapy for endometriosis has no improvement on pain relief or pregnancy rates, but a substantial decrease in endometriosis recurrence rate solely (30).…”
Section: Discussionmentioning
confidence: 99%